THE INFLUENCE OF ADVERTISING APPEALS, LIFESTYLE AND CELEBRITY ENDORSER ON THE DECISION TO USE THE DIGITAL KREDIVO CREDIT PLATFORM WITH BRAND IMAGE AS AN INTERVENING VARIABLE - Hana Mardhiyah Ar Rasyida Zahra; Dwi Sunu Kanto; Aam Bastaman (SEAN Institute, 2023)
This study aims to determine the effect of advertising appeals, lifestyle and celebrity endorser both partially and simultaneously on consumer’s usage decision in choosing credit digital platform Kredivo with brand image as intervening variable. The independent variables used in this study are advertising appeals (X1), lifestyle (X2) and celebrity endorser (X3), while the dependent variable is a usage decision (Y) and intervening variable is brand image (Z). the research method used in this study is quantitative research methods, by using a sample of 131 consumer Kredivo respondents in Jabodetabek areas. The sampling technique used in the survey is nonprobability sampling with accidental sampling type. The analytical method applied in this study is SEM PLS analysis using SmartPLS 3 software. The results of this study indicate that advertising appeals variable has no significant effect partially and simultaneously on the use decision variable, lifestyle variable has a partial mediating effect on the use decision variable and the celebrity endorser variable has a full mediating effect on the use decision variable.